Violência contra mulheres nas universidades: contribuições da produção científica para sua superação (Scielo e Web of Science 2016 e 2017). - Bellini, Daniela Mara Gouvêa (2018)
Gender violence is in every social structure, causing serious damage to the victim as well as to the people around. Statistics and studies show that the women are the main victims. More recently, research and reports have revealed that gender violence also happens at universities and, in them, women are the main target; furthermore, international studies already indicate intervention and prevention towards gender violence at universities. Following the reported shortage of academic studies found in Brazilian magazines, this research had as its main purpose to put in evidence the theoretical and empirical contributions, in the education scope, disseminated in national scientific as well as international articles about the gender violence issue in universities, highlighting violence towards women. Preventive measures have been searched or palliative indicated by them. Firstly, based on bibliographic research, a search has been conducted based on Scielo data, temporary cut by the low production recorded, and on the Web of Science data between the years 2016 and 2017. The recorded data was organized according to the area of knowledge, the target public complied with, the kind of violence suffered, the research methodology used in studies, the forward of the problematic and the approach of the article (preventive / palliative). Then, the collected information was submitted to analysis as to its excluding dimension and its transformative dimension, based on communicative methodology (Gomez et al, 2006), to point out knowledge and ways for the transformation of the latest context in the Brazilian universities. The main data found was: eight articles based on Scielo are from the health area. The predominant methodology research was the quantitative; about the kind of violence found were: physical, psychological, sexual and verbal, and physical being the most focused on. In the universities, inside the preventive approach, there are the specific formation proposals for awareness by the students. From the eighteen international articles analyzed on the Web of Science data were all from the education area. Five were qualitative, three quantitative and four quantitative and qualitative. There is a disparity between the focusing on the kind of violence, and physical violence being the most researched at the national base and the sexual violence the main focus of research at the international base. We have also identified that in Brazil there is no policy or specific legislations about the issue. From the analysis and literature studies a list of recommendations was generated for the prevention and the overcoming of violence against women at universities.